Adaptive Joint Interference Cancellation and Space-Time Block Decoding for IEEE 802.11b WLAN Systems - Jonietz, Christof; Gerstacker, Wolfgang; Rohde, Christian; Koch, Wolfgang; Schober, Robert (Conference Proceedings, 2006)
Digital transmission in wireless local area networks (WLANs) according to the IEEE 802.11b standard suffers from fading, intersymbol interference (ISI), and co-channel interference (CCI). In this paper, receivers with joint interference cancellation and time-reversal space-time block decoding (JICSTD) are proposed for an enhanced version of the IEEE 802.11b WLAN standard with space-time coded transmission. In IEEE 802.11b, complementary code keying (CCK) with a maximum data rate of 11 Mbit/s is employed as modulation format. The proposed receivers perform JICSTD in a first stage and equalization in a second stage. Minimum mean-squared error (MMSE-)JICSTD presuming perfect channel knowledge for all users and a training based least-squares (LS-)JICSTD for asynchronous interference are investigated, respectively. For subsequent equalization block-based reduced-state sequence estimation (RSSE) tailored for CCK transmission is used.<br
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.adapti
Keywords: Silicon; Adaptation model

Blanking Gaps in Uplink Cellular UMTS in the IMT-2000 Extension Band to Solve the Bluetooth Coexistence Problem - Konrad, Markus; Koch, Wolfgang (Conference Proceedings, 2006)
According to the ECC-PT1 the UMTS (Universal Mobile Telecommunications System) FDD (Frequency Division Duplex) uplink in the 2500-2690 MHz extension band starts at 2500 MHz. Bluetooth (BT) is operated in the 2.4 GHz ISM (Industrial, Scientific, and Medical) band. In [1] we have demonstrated that RF blocking is a severe source of interference to the BT technology if both technologies are co-located within the same terminal. Observing that Bluetooth devices transmit short packets followed by long transmission gaps and using the knowledge that the channel coded UMTS uplink spread spectrum signal is inherently robust to short gaps, we introduce the concept of UMTS uplink blanking gaps which refers to switching off the uplink transmission during mobile terminal BT reception as a solution to preventing RF receiver blocking by exploiting convolutions! coding (CC) and interleaving. By means of link level simulations the authors demonstrate that the loss due to blanking is comparable to the ĒB/N0 loss of UMTS compressed mode for both 12.2 kbit/s speech and 64.0 kbit/s data services and thus a reasonable solution to ensure coexistence. ©2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.blanki
Keywords: Blanking; 3G mobile communication; Bluetooth; Radio frequency; Frequency conversion; Cellular networks; Radiofrequency interference; Spread spectrum communication; RF Signals; Robustness

Coexistence Analysis of Bluetooth and Cellular UMTS in the 2500-2690 MHz Band - Konrad, Markus; Koch, Wolfgang; Huschke, Jörg (Conference Proceedings, 2006)
One of the key issues of next generation mobile communications is compatibility with other wireless standards to further enhance ubiquity. The 2500-2690 MHz band has been identified as extension band for IMT-2000 systems such as UMTS (Universal Mobile Telecommunications System). The 2.4 GHz ISM (Industrial, Scientific, and Medical) band is available for all kinds of unlicensed technologies such as Bluetooth (BT) and Wireless LAN (WLAN). The combination of BT and GSM within one mobile phone has become widely accepted, and therefore the same combination will be required to work for UMTS mobile phones operating in the 2.5 GHz extension band as well. Radio network simulations are performed for a variety of scenarios in order to analyze the performance of the integrated BT receiver while the UMTS uplink signal for frequency division duplex (FDD) mode is present. The objective of this work is to analyze the performance of the BT receive mode in terms of user satisfaction and outage probabilities for indoor use as worst case scenario. © 2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.coexis
Keywords: Bluetooth; 3G mobile communication; Wireless LAN; Mobile handsets; Performance Analysis; Mobile communication; Communication Standards; GSM; Radio Network; Analytical models

Cooperative mobile-to-mobile file dissemination in cellular networks within a unified radio interface - Popova, Larissa; Herpel, Thomas; Gerstacker, Wolfgang; Koch, Wolfgang (Computer Networks, 2008)
In this paper, a data dissemination technique is introduced for cellular networks by embedding peer-to-peer data transfer into the hierarchical architecture of UMTS (Universal Mobile Telecommunication Systems) for cooperative sharing of data among mobile terminals. Our concept is based on the uplink/downlink traffic imbalance in 3G wireless networks and clearly confirms the social principle "real egoistic behavior is to cooperate". It boosts the spectral efficiency of UMTS by enabling direct mobile-to-mobile data transfer and by dynamically allocating users to temporarily unused uplink channels. The results indicate a substantial increase in service probability and overall system throughput, as well as a significant reduction of the expected file download time. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IMMD.IMMD7.cooper
Keywords: Cooperative file dissemination; Spectral efficiency; Traffic imbalance; UMTS

Downlink Performance Improvements in (A)synchronous GPRS Networks using Single/Multiple Antenna Interference Cancellation Techniques - Popova, Larissa; Meyer, Raimund; Gerstacker, Wolfgang; Koch, Wolfgang (12th European Wireless Conference 2006 - Enabling Technologies for Wireless Multimedia Communications, 2011)
The aim of this paper is to assess GPRS data throughput of GSM networks for single and multiple antenna interference cancellation (SAIC/MAIC) receivers in the terminals. This is done by using a two-step top-down simulation methodology. Both synchronous and asynchronous networks with traditional European reuses of 1/3 and 3/9 are considered. It turns out that SAIC/MAIC receivers are very beneficial also for European network planning. The results indicate a substantial gain in data throughput in the order of 20-35% for SAIC compared to terminals with a conventional receiver. A further dramatic increase in throughput up to 120% can be achieved by terminals using an MAIC receiver. In spite of the widespread view that a maximum gain will be achieved for a synchronized network, where the amount of overlap between desired signal and interference can be controlled, our results show that the performance of both network types is very simila

Efficient supporting methods for adaptive pilot-aided channel estimation in OFDM systems - Rohde, Christian; Lipp, Stefan; Stadali, Holger; Gerstacker, Wolfgang; Koch, Wolfgang (18th International OFDM Workshop 2014, InOWo 2014, 2014)
Approaches for adaptive pilot-aided channel estimation in frequency domain are well established for orthogonal frequency-division multiplexing (OFDM) systems. To further enhance the performance of both the adaptive channel estimation and the entire receiver, three efficient supporting methods are discussed in this paper. First, the well-known concept of non-rectangular windowing is recalled due to its fundamental importance and benefits over the conventional rectangular windowing. Secondly, an approach is proposed to reduce the suboptimality of channel estimation algorithms applying real-valued filtering, which can even lead to convergence speed gains compared to complex-valued filtering in scenarios where real-valued filters are theoretically suboptimum. Third, a novel scheme treating continuous as scattered pilots (CASP) is introduced to solve the reference data problem of adaptive channel estimation algorithms. Simulation results for a scenario according to the hybrid satellite/terrestrial broadcasting system DVB-SH, show that these methods combine a low complexity with a noticeably increased receiver robustness.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Adaptive pilot-aided channel estimation; Block recursive least-squares (BRLS) algorithm; Enhanced real-valued filtering; Normalized block least-mean-square (NBLMS) algorithm; Orthogonal frequency-division multiplexing (OFDM); Treating continuous as scattered pilots (CASP)

Enhanced Downlink Capacity in UMTS supported by Mobile-to-Mobile Data Transfer - Popova, Larissa; Herpel, Thomas; Koch, Wolfgang (6th International IFIP-TC6 Networking Conference, 2007)
The goal of this work is first to analyze the feasibility of a peer-to-peer file sharing technique in mobile cellular environments, taking into account key characteristics and peculiarities of the UMTS Radio Access Network (UTRAN). The concept is referred here to as mobile-tomobile (m2m). Next, our research efforts explore the performance benefits of m2m file sharing applications in UMTS networks in terms of releasing overall downlink capacity, which can be used to provide better Quality of Service (QoS) for real-time services. To evaluate the performance of the proposed m2m concept we conducted extensive simulation studies with appropriately modified radio propagation models for low antenna heights for both, transmitter and receiver, as it is typical for m2m. Two alternative scenarios of serving user requests (m2m network mode and conventional UMTS mode) have been constructed and analyzed. The results indicate a dramatic increase in service probability and overall throughput gain of up to 85 % in a UMTS network, supported by the m2m data transmission mode. Furthermore, results show that by a well-designed m2m routing policy and proper utilization of currently not used uplink resources (due to asymmetric uplink/downlink traffic load) substantial reduction of the expected file download time can be achieved. © IFIP International Federation for Information Processing 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD7.enhanc
Keywords: Asymmetric uplink/downlink traffic load; Data exchange policy; Direct mobile-to-mobile data transfer; Released downlink capacity; Unified radio interface; WCDMA

Network coding assisted mobile-to-mobile file transfer - Popova, Larissa; Schmidt, Armin; Gerstacker, Wolfgang; Koch, Wolfgang (2007 Australasian Telecommunication Networks and Applications Conference, 2008)
This paper is a sequel of previous work, in which we have studied the problem of congestions on the typically overloaded downlink channels in UMTS (Universal Mobile Telecommunication System) networks. Our concept is based on the uplink/downlink traffic imbalance in 3G wireless networks and is realized by organizing seamless cooperation between peer-to-peer and cellular networks using a unified radio interface for both systems. The primary goal is to improve the spectral efficiency of cellular networks by enabling direct mobile-to-mobile (m2m) communication on temporarily unused uplink channels for the distribution of a large popular content in a non-real time multicast manner. The aim of this work is to further improve the interaction between cellular and peer-to-peer networks by generalizing the traditional scheduling paradigm. A network coding technique is embedded as a solution to the scheduling problem in the distributed dynamic environment of wireless large-scale networks. We investigate the performance of the system in terms of dependability of information distribution among m2m users. Simulations demonstrate the enhanced performance of the file distribution in terms of file download time. Furthermore, the obtained results highlight that network coding based m2m data transfer allows distribution of popular files to a large number of users while placing minimal bandwidth requirements on the central serve

On the Feasibility of UMTS-based Traffic Information Systems - Sommer, Christoph; Schmidt, Armin Christian; German, Reinhard; Dressler, Falko; Koch, Wolfgang; et al. (Ad Hoc Networks, 2010)
Intelligent Transportation Systems (ITS) are a hot topic in the communications society. Currently, research is primarily focusing on setting up Vehicular Ad Hoc Networks (VANETs) based on WLAN technology. However, VANETs are heavily dependent on high market penetration or infrastructure support. Third-generation (3G) networks might complement these efforts. They are already widely deployed and can serve as the basis for Car-to-Infrastructure (C2I) applications. We developed a simulation framework for holistic analysis of complex UMTS-based ITS. This framework couples simulation models with corresponding protocols of the UMTS link level, of higher network layers, and of road traffic. Based on our simulation framework and real-world 3G network coverage data, we evaluated a UMTS-based Traffic Information Systems (TIS) in a typical highway scenario in which information about traffic jams needed to be communicated to other cars for optimized route planning. The evaluation clearly outlines the capabilities of the simulation framework and evaluation results are consistent with all expectations. For example, we show that the availability of UMTS multicast distribution services are demanded for an efficient operation of the TIS application. © 2010 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2010.tech.IMMD.IMMD7.onthef
Keywords: Car-to-Infrastructure; Intelligent Transportation Systems; Performance modeling; UMTS

Robust MBSFN transmission using the Golden code - Konrad, Markus; Gerstacker, Wolfgang; Koch, Wolfgang (2009 International Conference on Ultra Modern Telecommunications & Workshops, 2009)
Multimedia broadcast over a single frequency network (MBSFN) has attracted a lot of interest recently. This paper is on Golden coded spatial multiplexing MBSFN transmission using a soft-output sphere decoder (SOSD) and the impact of such a transceiver on the block error rate (BLER) system performance. In total, we consider three transceiver types and evaluate their performance in cellular orthogonal frequency division multiplexing (OFDM) based MBSFN scenarios with urban characteristic taking into account single-cell broadcast and multi-cell broadcast with and without guard interval (GI) excess. In addition to the Golden coded system, we consider horizontal BLAST (H-BLAST) with decoded-feedback minimum mean-squared error (MMSE) successive interference cancelation (SIC) detector as a low complexity reference system, and a pure spatial multiplexing system with SOSD. The Golden coded transmission shows an increased overall robustness in an MBSFN network in comparison to the H-BLAST MMSE SIC reference system and in comparison to spatial multiplexing with SOSD, particularly in scenarios with high spectral efficiencies, i.e., high rates of the channel code. We demonstrate that this also applies for the critical case of an exceeded G